Explicating Correlates of Juvenile Offender Detention Length: The Impact of Race, Mental Health Difficulties, Maltreatment, Offense Type, and Court Dispositions - Mallett, Christopher A (2011)
Detention and confinement are widely acknowledged juvenile justice system problems which require further research to understand the explanations for these outcomes. Existing juvenile court, mental health, and child welfare histories were used to explicate factors which predict detention length in this random sample of 342 youth from one large, urban Midwestern county in the United States. Data from this sample revealed eight variables which predict detention length. Legitimate predictors of longer detention length such as committing a personal crime or violating a court order were nearly as likely in this sample to predict detention length as other extra-legal predictors such as race, court disposition for mental health problems, child welfare involvement, and child physical abuse victimization. Many of the factors that increase duration of detention are actually disadvantages that these youth endure; therefore preventative and intervention measures are in order